Self-efficacy among patients with chronic diseases and its associated factors - Shakya, Dayana (Journal of Kathmandu Medical College, 2018)
Background: Chronic diseases are in an increasing trend worldwide. Although, this rise may be due to a number of factors, one reason for the worldwide increase is due to better treatment protocols and higher awareness among patients. The management of chronic disease depends on the patient’s ability to alter the modifi able risk factors. The burden of disease can be decreased with better self- efficacy. Objectives: To assess the self-efficacy among patients with chronic diseases Methodology: In this descriptive, cross sectional study, data was collected purposively from 329 patients with chronic diseases presenting in the Medical outpatient department of Kathmandu Medical College. Face to face interview method was used to collect data using Chronic Disease Self-efficacy Scale and Patient Assessment Chronic Illness Care Questionnaire. Association with selected socio demographic variables were computed with Mann Whitney U and Kruskal Wallis H tests. Results: The mean age of the patients was 62±13 years. Males, those earning, those never admitted in the hospital for their disease and those who exercised were found to have better self-efficacy. There was significant difference in self-efficacy in terms of age, education, marital status, caregivers and body mass index. Self-efficacy showed significant positive correlation with monthly family income and health care provider score whereas significant negative correlation with age and monthly cost of treatment. Conclusion: Self-efficacy of patients with chronic disease can be improved with certain modifiable factors like daily exercise and appropriate body mass index. Younger patients, males, educated, employed and married patients were found to have better self-efficacy. Proper counselling by health care providers also improves self-efficacy.